Co-crystallization of an organic solid and a tetraaryladamantane at room temperature - Rami, Fabian; Nowak, Jan; Krupp, Felix; Frey, Wolfgang; Richert, Clemens (Beilstein Journal of Organic Chemistry, 2021)
Tetraaryladamantanes have proven useful as chaperones for the co-crystallization of small molecules that do not readily crystallize by themselves. The co-crystals are often useful for structure elucidation. Usually, the small molecules are encapsulated in the crystal lattice of the aryladamantane that forms during rapid thermal crystallization. Thus far, co-crystallization has been limited to liquids as guest molecules. Here we report the co-crystal structures of phenol, which is solid at room temperature, with both 1,3,5,7-tetrakis(2,4-dimethoxyphenyl)adamantane (TDA) and 1,3,5,7-tetrakis(2,4-diethoxyphenyl)adamantane (TEO). The co-crystals were obtained from solutions in dichloromethane by slow evaporation or diffusion. The implications for generating other co-crystals of two solids are briefly discussed.
Keywords: adamantanes; crystallization; organic solids; structure elucidation; X-ray crystallography